Fruit diversity and rarity in traditional markets of West Java, Indonesia - ADLI LUTHFIR RAHMAN YUWANA; BUDI IRAWAN; BUDIAWATI S. ISKANDAR; JOHAN ISKANDAR (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Yuwana ALR, Irawan B, Iskandar BS, Iskandar J. 2025. Fruit diversity and rarity in traditional markets of West Java, Indonesia. Biodiversitas 26: 6252-6272. Traditional markets play a crucial role in biodiversity conservation, particularly for local fruit species and landraces. However, the growing dominance of imported fruits has increasingly threatened the diversity of local fruits, underscoring the need to understand their current status in traditional markets. This study investigated the diversity and rarity of fruit species and landraces sold in three traditional markets: Gedebage, Ujungberung, and Tanjungsari (West Java, Indonesia) and examined traders’ knowledge regarding fruit uses and perceived reasons for their rarity. Data were obtained through a census, interviews, and direct observations and analyzed qualitatively and quantitatively using the Relative Frequency of Citation (RFC), Jaccard similarity indices, and Shannon-Wiener diversity indices. A total of 170 fruit entities (including fruit species and distinct landraces) were recorded (including 128 local), represent 59 botanical species from 28 families. Among these, 25 fruits were classified as rare due to unfavourable attributes, limited cultivation, land-use changes, and the influx of commercial commodities. Fruits with the highest RFC value were Cucumis melo (0.517), Carica papaya “California” (0.482), Musa acuminata (0.465), Citrus x aurantium “Medan” (0.413), and Musa x paradisiaca “Raja Cere”, “Ambon Bodas”, and “Ambon Lumut” (0.379). The study highlights traditional markets as valuable biodiversity observatories, reflecting the persistence and decline of local fruit diversity in rural agroecosystems. Strengthening their role in biodiversity monitoring and conservation planning can provide an effective, community-based approach to safeguarding local genetic resources.